A STUDY ON THE PRINCIPALS' AND ENGLISH TEACHERS' PERCEPTIONS ABOUT CURRICULUM 2013 AND ITS IMPLEMENTATION - Firmansyah, Eka (2015)
Curriculum is one of the important factors involved in teaching and learning process and it is the teacher who is the principle agent of curriculum development (Nunan, 1988). The implication of the curriculum development is that the teachers have sufficient chances to advance their professionalism and self determination. Moreover, principals play a vital and ever-expanding role in the process of curriculum development (Glatthorn, 2009). In relation to the principals' role and teachers' chances in developing K-13, it seems essential to look into the principals' and English teachers' perceptions on building up this most recent curriculum. Therefore, this study is aimed at describing the various principals' and English teachers' perceptions about K-13 and its implementation, and also it investigates English teachers' problems and solutions in developing K-13. The participants of this study were six principals and thirty English teachers in Bandung. This study employed quantitative and qualitative methods (mixed methods), thus two types of data collection techniques were applied. Quantitative data were collected first through survey using Guttman and Lickert scale questionnaires to explore principals' and English teachers' perceptions on the implementation of K-13. To get in-depth information about English teachers' perceptions, problems, and solutions on the implementation of K-13, a qualitative data were also collected through an interview. In general, it was uncovered that almost all principals perceived their role in the implementation of K-13 positively. It's apparent that they were committed to do their roles well. Meanwhile, not all English teachers knew the concept of K-13 and how it was developed, and it has affected their perceptions on developing K-13. Furthermore, the English teachers still faced some problems in developing K-13. However, this study was conducted in a short time and limitations were obviously inevitable, it's recommended that other researchers conduct the next research on the area of K-13 recurrently. It is expected that by doing the further research in the same field regularly, it will keep the trustworthiness of an issue.